Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How do I evaluate this limit?

$$\lim_{n\to+\infty}\sum_{k=1}^{n} \frac{1}{k(k+1)\cdots(k+m)} \qquad (m=1,2,3,\cdots)$$

Thanks in advance.

share|cite|improve this question
Do you want to evaluate this for arbitrary $m$? – Chris Taylor Jan 28 '12 at 13:39
yes for arbitrary m – FrConnection Jan 28 '12 at 13:51
Note that if we multiply by $m(m!)$, we get the probability mass function of the Yule-Simon distribution with parameter $m$. (In the general Yule-Simon, $m$ is positive but not necessarily an integer, so the probability mass function is expressed in terms of the gamma function.) The value of your limit says that the Yule-Simon really is a pmf. – André Nicolas Jan 28 '12 at 16:45
up vote 6 down vote accepted

Put $s_{n,m}=\sum_{k=1}^n\frac 1{k(k+1)\ldots (k+m)}$. We have for $m\geq 2$ \begin{align*} s_{n,m}&=\frac 1m\sum_{k=1}^n\frac{k+m-k}{k(k+1)\ldots (k+m)}\\ &=\frac 1m \left(s_{n,m-1}-\sum_{j=2}^{n+1}\frac 1{j\ldots (j-1+m)}\right)\\ &=\frac 1m\left(s_{n,m-1}-s_{n+1,m-1}+\frac 1{1\cdots (1-1+m)}\right)\\ &=\frac{s_{n,m+1}-s_{n+1,m-1}+\frac 1{m!}}m, \end{align*} and since the series $\sum_{k\geq 1}\frac 1{k(k+1)\ldots (k+m-1}$ is convergent, $\lim_{n\to \infty}s_{n,m+1}-s_{n+1,m-1}=0$ so $\lim_{n\to\infty}s_{n,m}=\frac 1{m\cdot m!}$. This formula also works for $m=1$ by a direct computation.

share|cite|improve this answer

Rewriting the term in the sum with factorials, notice that $$\frac{1}{k(k+1)\cdots(k+m)}=\frac{1}{m!}\left(\frac{(k-1)!m!}{(k+m)!}\right).$$ Then since $$\frac{(k-1)!m!}{(k+m)!}=\int_0^1 x^{k-1} (1-x)^m dx,$$ which can be proved by induction or by using a property of the Beta Function, we see that $$\sum_{k=1}^\infty \frac{1}{k(k+1)\cdots(k+m)}=\sum_{k=1}^\infty \left(\frac{1}{m!} \int_0^1 x^{k-1} (1-x)^m dx\right)$$ $$=\frac{1}{m!}\int_0^1 (1-x)^m\left( \sum_{k=1}^\infty x^{k-1} \right)dx=\frac{1}{m!}\int_0^1 (1-x)^{m-1}dx$$

$$=\frac{1}{m! m}.$$

share|cite|improve this answer

Here is an answer without beta functions. Note that the residue of $$f(z) = \frac{1}{z(z+1)\cdots(z+m)}$$ at $z=-q$ is $$\mathrm{Res}(f(z); z=-q) =\frac{1}{(-q)(-q+1)\cdots(-q+(q-1))(-q+(q+1))\cdots(-q+m)}$$ which is $$\frac{(-1)^q}{q!\times (m-q)!} = \frac{(-1)^q}{m!} {m\choose q}.$$ Hence by the residue method for partial fractions we get that $$f(z) = \frac{1}{m!} \sum_{q=0}^m {m\choose q} (-1)^q \frac{1}{z+q}.$$ Apply this to the sum to obtain $$\sum_{k=1}^\infty \frac{1}{k(k+1)\cdots(k+m)} = \frac{1}{m!} \sum_{k=1}^\infty \sum_{q=0}^m {m\choose q} (-1)^q \frac{1}{k+q}.$$ Now ask what the coefficient is of the term $1/(k+q) = 1/p$ to get $$\frac{1}{m!} \sum_{p=1}^\infty \frac{1}{p}\sum_{q=0}^{p-1} {m\choose q} (-1)^q.$$ Observe that when $p-1\ge m$ the inner sum becomes zero, so that we are left with $$\frac{1}{m!} \sum_{p=1}^m \frac{1}{p}\sum_{q=0}^{p-1} {m\choose q} (-1)^q.$$ It therefore remains to evaluate the sum term. We seek to show that $$\frac{1}{m} =\sum_{p=1}^m \frac{1}{p}\sum_{q=0}^{p-1} {m\choose q} (-1)^q.$$

This is the moment to apply what H. Wilf terms the 'snake oil' method in his famous text on generating functions. (Consult this Mathworld Entry.) Introduce the univariate generating function $$g(z) = \sum_{m\ge 1} z^m \sum_{p=1}^m \frac{1}{p}\sum_{q=0}^{p-1} {m\choose q} (-1)^q = \sum_{p=1}^\infty \frac{1}{p} \sum_{m=p}^\infty z^m \sum_{q=0}^{p-1} {m\choose q} (-1)^q \\ = \sum_{p=1}^\infty \frac{z^p}{p} \sum_{m=0}^\infty z^m \sum_{q=0}^{p-1} {m+p\choose q} (-1)^q.$$

Now observe that $$ \sum_{q=0}^{p-1} {m+p\choose q} (-1)^q = (-1)^{p-1} {m+p-1\choose p-1}$$ as can be seen by induction on $m$, which we now carry out.

For $m=0$ we get equality with $$\sum_{q=0}^{p-1} {p\choose q} (-1)^q = -(-1)^p = (-1)^{p-1} {p-1\choose p-1}.$$ and for the induction step we have $$ \sum_{q=0}^{p-1} {m+1+p\choose q} (-1)^q = 1 + \sum_{q=1}^{p-1} {m+1+p\choose q} (-1)^q \\= 1 + \sum_{q=1}^{p-1} {m+p\choose q} (-1)^q + \sum_{q=1}^{p-1} {m+p\choose q-1} (-1)^q \\= (-1)^{p-1} {m+p-1\choose p-1} - \sum_{q=0}^{p-2} {m+p\choose q} (-1)^q \\ = (-1)^{p-1} {m+p-1\choose p-1} - \sum_{q=0}^{p-1} {m+p\choose q} (-1)^q + (-1)^{p-1} {m+1+p-1\choose p-1} \\ = (-1)^{p-1} {m+1+p-1\choose p-1}.$$

Returning to $g(z)$ we thus obtain $$g(z) = \sum_{p=1}^\infty \frac{z^p}{p} \sum_{m=0}^\infty z^m (-1)^{p-1} {m+p-1\choose p-1} = - \sum_{p=1}^\infty \frac{z^p}{p} (-1)^p \frac{1}{(1-z)^p}$$ by the Newton binomial.

Finally recall that $$\log\frac{1}{1-z} = \sum_{q\ge 1} \frac{z^q}{q}$$ so that $g(z)$ simplifies to $$ -\log\frac{1}{1+z/(1-z)} = -\log\frac{1-z}{1-z+z} = -\log(1-z) = \log\frac{1}{1-z}.$$ Therefore $$[z^m] g(z) = \frac{1}{m}$$ and we are done.

There is a similar but not quite identical computation at this MSE link.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.